Analysis of Suspense Types in Narrative Texts by Third-Semester Students at HKBP Nommensen University - pane, Angela; shakila, angela (Journal Of Education, 2024)
This research examines third semester students' narrative writing with tension in the English Language Education Program at HKBP Nommensen Pematangsiantar University. This research sought students' perspectives on how they integrate tension in narratives – especially situational, psychological, and anticipatory elements. This research uses a qualitative strategy that examines 40 narrative texts to determine the type of tension and its occurrence as well as its level of significance. The results showed that anticipatory tension was the most common type, followed by situational, conflict-based, and psychological tension. This research also expands the scope of the discipline of narrative writing, especially creative story pieces to be included in curriculum activities for students.